PENGARUH CURRENT RATIO DAN DEBT TO EQUITY TERHADAP RETURN ON ASSET PADA PERUSAHAAN SUB SEKTOR PERHUTANAN DAN KERTAS YANG TERDAFTAR DI BEI - Aulia, Nur; Nurulrahmatiah, Nafisah; Rahmatiah, Rahmatiah (Jurnal Manajemen, 2024)
Forestry and paper sub-sector companies are required to be able to compete with other industrial groups and similar industries in facing global market competition and must pay attention to one important factor, namely their financial performance. This research aims to determine the influence of the Current Ratio and Debt to Equity Ratio on Return On Assets in forestry and paper sub-sector companies listed on the IDX. This type of research is associative using a list of tables as a research instrument. are all forestry and paper sub-sector companies registered on the IDX from 2018-2022, namely 6 companies. The sample in this research was 4 forestry and paper sub-sector companies listed on the IDX from 2018-2022. The sampling technique used is purposive sampling. The data collection techniques used in this research are documentation techniques and literature study. The data that has been collected is then analyzed using the classic assumption test, multiple linear regression, correlation coefficient, determination test, t test and f test. The research results show that the Current Ratio and Debt to Equity Ratio have a significant simultaneous effect on Return On Assets in forestry and paper sub-sector companies listed on the IDX.